What do we need for a gender-sensitive Covid-19 response in agriculture and food security? Research tools to assess women's empowerment - Ringler, Claudia (2020)
Claudia Ringler POLICY SEMINAR Virtual Event - What do we need for a gender-sensitive Covid-19 response in agriculture and food security? Insights from research and practice MAY 21, 2020 - 09:30 AM TO 10:45 AM EDT